(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A primary labelling of a graph with n vertices is a labelling of its vertices in a manner that the labels of each two adjacent vertices are relatively primitive with unique numbers of 1,2, . . . , n. T. Varkey suspected of prime labelling in the ladder graphs. That’s what we prove. in this conjecture.